Influence of wheel size on muscle activity and tri-axial accelerations during cross-country mountain biking - Hurst, H. T.; Sinclair, J.; Atkins, S.; Rylands, L.; Metcalfe, J. (Journal of Sports Sciences, 2017)
This study aimed to investigate the influence of different mountain bike wheel diameters on muscle activity and whether larger diameter wheels attenuate muscle vibrations during cross-country riding. Nine male competitive mountain bikers (age 34.7 ± 10.7 years; stature 177.7 ± 5.6 cm; body mass 73.2 ± 8.6 kg) participated in the study. Riders performed one lap at race pace on 26, 27.5 and 29 inch wheeled mountain bikes. sEMG and acceleration (RMS) were recorded for the full lap and during ascent and descent phases at the gastrocnemius, vastus lateralis, biceps brachii and triceps brachii. No significant main effects were found by wheel size for each of the four muscle groups for sEMG or acceleration during the full lap and for ascent and descent (P > .05). When data were analysed between muscle groups, significant differences were found between biceps brachii and triceps brachii (P < .05) for all wheel sizes and all phases of the lap with the exception of for the 26 inch wheel during the descent. Findings suggest wheel diameter has no influence on muscle activity and vibration during mountain biking. However, more activity was observed in the biceps brachii during 26 inch wheel descending. This is possibly due to an increased need to manoeuvre the front wheel over obstacles.